Dose Verification Of Brass Mesh Bolus For Contralateral Breast Post-mastectomy In Three-dimensional Conformal Radiotherapy Technique - Buang, Sakinah (2023)
Post mastectomy radiation therapy (PMRT) prescribed to patient that undergo breast mastectomy. With the bolus application in PMRT, it has shown few limitations whereby current water equivalent bolus (WEB) unable to conform irregular surface consistently. Besides that, dose inhomogeneity arises in contralateral breast (CB) and organ at risk (OAR) during PMRT. It is established that brass mesh bolus (BMB) has potential in conforming irregular surface with the aim to treat chest wall site in delivering maximum dose and sparing OAR. This study aims to determine the feasibility of BMB as an alternative to bolus and to verify dose received by CB and target breast with application of BMB in 3-dimensional conformal radiation therapy (3DCRT). This study are designed based on three main parts ; firstly is to characterize dosimeters (Ludlum detector, ionization chamber and nanoDotTM) based on Cobalt-6o and 6-MV photon energy; secondly is to measure the radiological, physical and dosimetric properties of BMB by measuring the density using three methodologies (Image-J analysis, conventional density and CT analysis), mass attenuation coefficient, mass energy absorption coefficient and percentage depth dose (PDD) ; and lastly is to verify the radiotherapy treatment with the BMB to the PMRT heterogenous phantom by 3DCRT. Statistical analysis evaluation in accordance with the international standard was applied. The results revealed that all dosimeters have high linearity with acceptable traceability